Prevalence of overweight and obesity among school children in Mysuru, Karnataka - Usha M Thomas; D Narayanappa; M S Sujatha (Journal of Family Medicine and Primary Care, 2021)
Childhood obesity has become a major public health challenge in developing countries including India due to the changes in the lifestyle and food habits of children owing to the influence of urban culture and technological growth. The present study is a cross-sectional, school-based study conducted to assess the prevalence of obesity and to determine the demographic variables influencing the obesity among school children. Methods: The study included 440 students (Boys: 240, Girls: 200) from two randomly selected schools of Mysuru city, Karnataka. WHO Standard Age and Sex specific Growth Reference charts were used for defining overweight and obesity. Modified Kuppuswamy's socioeconomic scale (2019) was adopted to assess the socioeconomic status of the family. Results: Obesity prevalence among the study subjects was 3.86% and overweight was 12.27%. The mean body mass index (BMI) among boys was 18.13 and girls was 18.80. The difference in the distribution of BMI between male and female groups was statistically significant (P = 0.023). Age and obesity status of the children was found to have a significant association (P = 0.022). Prevalence of overweight and obesity was more among children from higher socioeconomic class (P = 0.01). Conclusion: Prevalence of obesity and overweight among school children is comparatively higher. The higher familial income, dietary patterns, parental history of obesity and diabetes and having urban residence were identified as the major factors which influenced the obesity status of the school children.